Analysis of the spatial and temporal variability of irrigated maize yield. - Marques da Silva, José Rafael (2006)
The quantitative analysis of the yield of seven irrigated plots of land sown with maize was carried out over a period of 3 yr in order to determine the spatial and temporal variability. The methodology used was based on: inter-annual analysis of yield, which quantifies the overall difference in production from 1 yr to the next; and temporal variance, which indicates the variability of yield at a given point over time. The results show that even with irrigated crops, where production factors are generally subject to high degree of control, there is a high degree of inter-annual variability, becoming less marked over time. These results enable an investment risk map associated with a given crop and a given plot to be drawn; they also enable it to be shown that the sum of the yield for stable zones for each field decreases as field area increases, indicating that the greater the length of the centre pivot irrigator used, the lower the temporal stability of yield. The most stable yields are associated with an average distance of about 15m from the flow lines; finally, the results show that forecasting for future years is extremely difficult owing to the fact that the temporal variability of yield may vary between 1 and 8 t/ha.